Masculinity in Ahmadou Kourouma's The Suns of Independence - Chiliboyi, Obed (My University, 2010)
ABSTRACT The study examines the construction of African masculinities as portrayed in Ahmadou Kourouma’s novel The Suns of Independence. The study relies on theories of Robert Morrell, Andrea Cornwall, David Mills, Richard Ssewakiryanga, Robert Connell and Frank Salomane amongst others in identifying masculinities in the novel. Different definitions of masculinity have been given but the study hinges on Morrell’s definition. Chapter one introduces the study and gives the aim, background and contextualises the masculinities discussed in the study. Chapter two looks at the power and masculinities of traditional leaders such as praise singers, fetish priests and hunters and how these lost their power after independence. Chapter three focuses on the factors that led to the emasculation of Fama and how Salimata constructs female masculinity. Chapter four looks at religion and politics as two sites where tradition and modernity interacted and influenced construction, reconstruction and/or deconstruction of African masculinities. Chapter five summarises the preceding chapters.